Successful Complete Response of Tumor Thrombus after Combined with Chemotherapy and Irradiation for Ewing Sarcoma. (21st January 2018) - Minami, Yusuke; Matsumoto, Seiichi; Ae, Keisuke; Tanizawa, Taisuke; Hayakawa, Keiko; Funauchi, Yuki; Okumura, Sakae; Takazawa, Yutaka
Abstract : Pelvic Ewing sarcoma is associated with a worse prognosis. Thromboembolic events are relatively common in pediatric patients with cancers including sarcomas. We have presented a case of Ewing sarcoma arising from the left iliac bone with tumor thrombus of inferior vena cava (IVC) which was obtained complete response by both chemotherapy and irradiation. Magnetic resonance imaging (MRI) scan demonstrated that the tumor arising from the left iliac bone extended into the left side of sacral bone, suggesting the difficulty of surgical resection. Computed tomography (CT) revealed the existence of the tumor thrombus of IVC. We performed irradiation (31.2 Gy) and chemotherapy (combination of VCR, Act-D, IFM, and ADR). The tumor was controlled successfully, and the tumor thrombus of IVC has completely vanished. Four years after the treatment, coin lesion in the left upper lung appeared. Suspected of metastasis, segmental resection of the left upper lung was performed. Fourteen years after the surgery, the patient has been remained free of recurrence. It is clinically significant for surgeons to treat pelvic Ewing sarcoma with tumor thrombus.